Prevalence of Food Consumption and Diversification Among People having Lifestyle Diseases (Indian Journal of Extension Education, 2021)
Lifestyle diseases are the serious threat among adults. Most of the people in India are suffering from more than one form of diseases mainly type II diabetes mellitus, hypertension, obesity, constipation etc. To combat this, one of the foremost ways is to take proper food at apparent time in adequate amount. For the study, 40 subjects (21 male and 19 female) above 45 years were selected from Pusa block or university campus on the basis of occurrence of lifestyle diseases. Proper schedule was prepared consisting questionnaire related to their general information, food habits, anthropometric details, physiological and biochemical parameters. Information collected through personal interview. Dietary intake of both the subjects was recorded by using 24 h dietary recall method for 2 consecutive days. However, observed value of dietary nutrient (energy, protein, total fat, carbohydrates and sodium) intake were more than the recommended because of overconsumption. Therefore, only good nutrition and healthy lifestyle that is proper balanced diet, physical exercise, adequate sleep, reduced stress, well-adjusted biological clock, avoidance of fast and processed foods etc. will be followed by people regularly which helps to defeat the lifestyle consequences.